ERAD and how viruses exploit it - Byun, Hyewon; Gou, Yongqiang; Zook, Adam; Lozano, Mary M.; Dudley, Jaquelin P. (Frontiers in Microbiology, 2014)
Endoplasmic reticulum-associated degradation (ERAD) is a universally important process among eukaryotic cells. ERAD is necessary to preserve cell integrity since the accumulation of defective proteins results in diseases associated with neurological dysfunction, cancer, and infections. This process involves recognition of misfolded or misassembled proteins that have been translated in association with ER membranes. Recognition of ERAD substrates leads to their extraction through the ER membrane (retrotranslocation or dislocation), ubiquitination, and destruction by cytosolic proteasomes. This review focuses on ERAD and its components as well as how viruses use this process to promote their replication and to avoid the immune response.